Temperature shrinkage cracking resistant low-carbon concrete and preparation method thereof

By using chopped basalt fiber-loaded carbon ball composite materials and modified steel slag powder in large volume concrete, the temperature shrinkage crack problem is solved, efficient crack resistance and preparation of low-carbon concrete are achieved, and the service performance of concrete is improved. Service life.

CN119263729APending Publication Date: 2025-01-07JIANGSU XUMA NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411380941.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The problem of temperature shrinkage cracks caused by temperature differences after construction of large-volume and large-area concrete is caused by temperature differences. The existing technology has the problem of high cooling water cost and the compensatory shrinkage technology requiring precise wet curing, which affects the service performance and service life of concrete.

Method used

Using chopped basalt fiber-loaded carbon ball composite material and modified steel slag powder, a crack-resistant material with high binding strength was prepared through hydrothermal reaction, and combined with a retarder and a water reducer to prepare a low-carbon concrete that resists temperature shrinkage cracking. , limit the expansion of temperature shrinkage cracks and compensate for concrete temperature shrinkage.

Benefits of technology

It effectively reduces the risk of temperature shrinkage and cracking of concrete, improves crack resistance and strength, reduces the cost of cooling water, and improves the low-carbon performance and temperature shrinkage resistance of concrete through modified steel slag powder.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005069889260000121
    Figure BDA0005069889260000121
Patent Text Reader

Abstract

The invention relates to the technical field of concrete, in particular to temperature shrinkage cracking resistant low-carbon concrete and a preparation method thereof. The temperature shrinkage cracking resistant low-carbon concrete is prepared from the following raw materials in parts by weight: 200 to 220 parts of gel material, 340 to 380 parts of fine aggregate, 420 to 450 parts of coarse aggregate, 18 to 25 parts of chopped basalt fiber loaded carbon sphere composite material, 1.2 to 1.5 parts of retarder, 0.8 to 1.3 parts of polycarboxylate superplasticizer and 67 to 72 parts of water, the gel material comprises the following raw materials in percentage by weight: 30-35% of modified steel slag powder, 1-5% of fly ash and the balance of cement. According to the concrete, the short-cut basalt fiber is used for loading the carbon sphere composite material, expansion of temperature shrinkage cracks can be effectively limited, the replacement rate of cement by steel slag powder in the low-carbon concrete is effectively increased by further modifying the steel slag, meanwhile, f-CaO in the steel slag powder can be reasonably utilized, temperature shrinkage of mass concrete can be compensated, and the concrete has a good thermal insulation effect. The crack resistance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, and in particular to a low-carbon concrete resistant to thermal shrinkage cracking and a preparation method thereof. Background Art

[0002] In infrastructure construction, large-volume and large-area concrete projects are increasing. The heat released by cement hydration causes the volume to expand after pouring. After demolding, the internal heat storage of concrete causes the temperature difference between the concrete and the ambient temperature to be greater than 25°C, resulting in temperature shrinkage cracks, which affects the service performance of concrete, such as carbonation resistance, freeze-thaw resistance, and chloride ion resistance, and seriously shortens the service life of infrastructure. Therefore, the research and development of large-volume and large-area concrete temperature shrinkage crack prevention technology is of practical significance to improving the overall service performance of infrastructure and engineering safety. The main technical approaches for shrinkage reduction and crack prevention of large-volume and large-area concrete at home and abroad are as follows:

[0003] (1) By pre-arranging a water cooling system inside the concrete, circulating cooling water is used for cooling after the concrete construction and curing process, and the difference between the internal temperature of the large volume concrete and the ambient temperature is controlled within 25°C in accordance with the current specifications.

[0004] (2) By improving the plastic strength and yield stress of fresh concrete, its plastic shrinkage and early crack formation are reduced. The main technical measures are to add fibers and integrate admixture application technology to limit the expansion of temperature shrinkage cracks.

[0005] (3) By using shrinkage compensation technology, large-volume concrete can produce a volume expansion of 100-150 microstrains under the restriction of steel bars before demolding, thereby compensating for the temperature shrinkage after demolding, thereby effectively improving the concrete's crack resistance.

[0006] In the existing large-volume and large-area concrete construction, a variety of anti-cracking methods have been formed at home and abroad and have been applied in engineering practice. However, there are still various problems with the existing technology. For example, the cooling cost of cooling water is high, and the support of accurate finite element calculation is required. The water pipe layout is guided by the calculation results; the application of compensation shrinkage technology requires enhanced wet curing. If the curing is improper, it may even aggravate the cracking. Therefore, the development of improved admixture fiber combined with suitable admixtures is an effective technical means to solve the problem of temperature shrinkage cracking of large-volume and large-area low-carbon concrete. Summary of the invention

[0007] The purpose of the present invention is to provide a low-carbon concrete resistant to thermal shrinkage cracking and a preparation method thereof. The concrete utilizes short-cut basalt fibers loaded with carbon ball composite materials, which can effectively limit the expansion of thermal shrinkage cracks, and further improves the replacement rate of steel slag powder for cement in low-carbon concrete by modifying steel slag. At the same time, the f-CaO in the steel slag powder can be reasonably utilized to compensate for the thermal shrinkage of large-volume concrete and improve the crack resistance.

[0008] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0009] A low-carbon concrete resistant to thermal shrinkage cracking comprises the following raw materials in parts by weight: 200-220 parts of gel material, 340-380 parts of fine aggregate, 420-450 parts of coarse aggregate, 18-25 parts of short-cut basalt fiber-loaded carbon ball composite material, 1.2-1.5 parts of retarder, 0.8-1.3 parts of polycarboxylate water reducer and 67-72 parts of water.

[0010] Preferably, the gel material comprises the following raw materials in weight percentage: 30-35% of modified steel slag powder, 1-5% of fly ash, and the balance of cement.

[0011] Preferably, the method for preparing the modified steel slag powder comprises the following steps:

[0012] S1: Mix quicklime and white slag in a mass ratio of 7-8:2-3 to obtain a regulator;

[0013] S2: The steel slag is mixed evenly with a regulator of 17-20% of the mass of the steel slag, and then placed in a reaction furnace, heated to 1240-1260°C, and kept warm for 30-40 minutes, and then cooled to room temperature; the obtained steel slag is then crushed and ball-milled to obtain steel slag powder;

[0014] S3: weighing 1-1.5% of the total mass of the steel slag powder as a silane coupling agent;

[0015] S4: First weigh 3-4% of steel slag powder, then add silane coupling agent, mix evenly, and then mix with the remaining amount of steel slag powder in a ball mill to obtain the modified steel slag powder.

[0016] Preferably, the content of f-CaO in the steel slag powder is 2.7-3.2%; the specific surface area of ​​the modified steel slag powder is 500-560m 2 / kg;

[0017] The silane coupling agent is one or more of γ-glycidyloxypropyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane.

[0018] Preferably, the cement is silicate cement, and the fly ash is Class I fly ash or Class II fly ash.

[0019] Preferably, the method for preparing the chopped basalt fiber-loaded carbon sphere composite material comprises the following steps:

[0020] (1) pretreating the chopped basalt fibers to obtain pretreated chopped basalt fibers;

[0021] (2) dispersing the pretreated chopped basalt fibers in a 0.5-1 mol / L glucose aqueous solution, stirring and mixing, transferring the mixture to a reactor, sealing the reactor, and first performing a hydrothermal reaction at 190-200° C. for 40-48 h; then cooling the mixture to room temperature, and filtering the mixture to obtain an intermediate product;

[0022] (3) The intermediate product is then dispersed in a 0.1-0.3 mol / L glucose aqueous solution, stirred and mixed, and then transferred to a reactor. The reactor is sealed and first subjected to a hydrothermal reaction at 160-170° C. for 10-12 h. The mixture is then cooled to room temperature, filtered, washed with water, and vacuum dried to obtain a chopped basalt fiber-loaded carbon ball composite material.

[0023] Preferably, the step (1) specifically includes the following steps: the chopped basalt fiber is first placed in hydrochloric acid with a concentration of 2-3 mol / L and heated to 45-50°C for 3-4 hours, filtered and washed with water, and then placed in a sodium hydroxide solution with a concentration of 1-1.5 mol / L for 30-50 minutes, and then filtered, washed with water, and dried to obtain pretreated basalt fiber. By pretreating the chopped basalt fiber, the surface roughness of the chopped basalt fiber can be improved, and the surface active sites can be increased, thereby increasing the bonding strength between the chopped basalt fiber and the carbon ball.

[0024] Preferably, the length of the chopped basalt fibers is 4.5-5.5 mm, and the diameter is 13-16 μm. In addition, in steps (2) and (3) of the above preparation method, the mass ratio of the glucose aqueous solution to the pretreated chopped basalt fibers can be 25-50:1.

[0025] Preferably, the fine aggregate is composed of river sand and machine-made sand in a mass ratio of 1-2:1-2;

[0026] The fineness modulus of the river sand is 2.6-2.8; the fineness modulus of the machine-made sand is 2.7-2.9;

[0027] The coarse aggregate is 5-25 mm continuously graded crushed stone;

[0028] The retarder is sodium gluconate.

[0029] As a general inventive concept, the present invention provides a method for preparing low-carbon concrete resistant to thermal shrinkage cracking, comprising the following steps:

[0030] Add water to the gel material and stir for 4-5 minutes, then add fine aggregate and coarse aggregate, continue stirring for 4-5 minutes, then add short-cut basalt fiber-loaded carbon ball composite material, retarder, and polycarboxylate water reducer, stir and mix for 3-4 minutes to obtain the thermal shrinkage cracking resistant low-carbon concrete.

[0031] The beneficial effects of the present invention are:

[0032] 1. The present invention adds an appropriate amount of short-cut basalt fiber-loaded carbon ball composite material to concrete as an anti-crack fiber material, wherein the carbon ball is loaded on the surface of the short-cut basalt fiber, and the main body of the carbon ball basically does not react with the components in the concrete, and has a certain porosity. When the short-cut basalt fiber-loaded carbon ball composite material is dispersed in the concrete, the carbon ball can play an anchoring role, and the carbon ball is tightly combined with the concrete matrix, so that the short-cut basalt fiber-loaded carbon ball composite material and the concrete have a strong mechanical bite force, thereby effectively reducing the temperature shrinkage cracking of the concrete. In addition, the short-cut basalt fiber itself can also significantly improve the strength of the concrete, so it is beneficial to resist the tensile stress caused by temperature changes, and it can effectively slow down the formation and development of cracks, thereby reducing the risk of cracking as a whole and maintaining the structural integrity of the concrete.

[0033] 2. When preparing the short-cut basalt fiber-loaded carbon ball composite material, the present invention first places it in a high-concentration glucose aqueous solution for a long hydrothermal reaction to load larger carbon balls on the surface of the short-cut basalt fiber to enhance the interlocking force. Then, a shorter hydrothermal reaction is carried out in a low-concentration glucose aqueous solution to increase the roughness of the composite material surface, further enhance the bonding strength between the composite material and the concrete, and enable the short-cut basalt fiber-loaded carbon ball composite material to exhibit excellent crack resistance.

[0034] 3. The gel material used in the present invention contains a large amount of modified steel slag powder, which makes the concrete more low-carbon and environmentally friendly. The modified steel slag powder is prepared by high-temperature reconstruction of a regulator composed of quicklime and white slag and modified by a silane coupling agent. The gel activity of the steel slag powder obtained by high-temperature reconstruction by the method of the present invention is improved, which can enhance the strength of the concrete. At the same time, the modified steel slag powder also has a certain content of f-CaO, and its particle size is suitable. By stimulating the early hydration activity of f-CaO in the steel slag powder and utilizing the characteristics of volume expansion caused by hydration of f-CaO in the steel slag powder, a compensating shrinkage and crack resistance ability is formed during the construction period. The steel slag powder obtained by high-temperature reconstruction is modified by a silane coupling agent. On the one hand, the workability of the steel slag powder in concrete can be improved, and the steel slag powder can be more dispersed in concrete. On the other hand, it can fill pores, reduce cracks, etc., and improve the concrete's resistance to temperature shrinkage cracking.

[0035] 4. The present invention also adds an appropriate amount of retarder sodium gluconate, which delays the early hydration of cement minerals and cooperates with other raw materials to minimize the internal temperature difference, surface temperature difference and thermal shrinkage of large-volume concrete.

[0036] 5. The concrete of the present invention utilizes short-cut basalt fibers loaded with carbon ball composite materials, which can effectively limit the expansion of temperature shrinkage cracks, and further improves the replacement rate of steel slag powder for cement in low-carbon concrete by modifying the steel slag. At the same time, the f-CaO in the steel slag powder can be reasonably utilized to compensate for the temperature shrinkage of large-volume concrete and improve the crack resistance. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Embodiment 1:

[0039] A method for preparing modified steel slag powder comprises the following steps:

[0040] S1: Mix quicklime and white slag in a mass ratio of 8:2 to obtain a regulator;

[0041] S2: Steel slag (f-CaO content of 4.2wt%) and a regulator of 17% by weight of the steel slag are mixed evenly and placed in a reaction furnace, heated to 1240°C, kept warm for 35 minutes, and then cooled to room temperature; the obtained steel slag is then crushed and ball-milled to obtain steel slag powder. The steel slag powder is tested to have an f-CaO content of 3.0wt% and a specific surface area of ​​560m 2 / kg;

[0042] S3: weigh γ-glycidyloxypropyltrimethoxysilane which is 1.5% of the total mass of the steel slag powder;

[0043] S4: First weigh 4% of steel slag powder, then add γ-glycidyloxypropyltrimethoxysilane, mix evenly, and then put it in a ball mill with the remaining amount of steel slag powder for 1 hour to obtain modified steel slag powder.

[0044] Embodiment 2:

[0045] A method for preparing modified steel slag powder comprises the following steps:

[0046] S1: Mix quicklime and white slag in a mass ratio of 7:3 to obtain a regulator;

[0047] S2: Steel slag (f-CaO content of 4.2wt%) and a regulator of 20% by weight of the steel slag are mixed evenly and placed in a reaction furnace, heated to 1260°C, kept warm for 40 minutes, and then cooled to room temperature; the obtained steel slag is then crushed and ball-milled to obtain steel slag powder. The steel slag powder is tested to have an f-CaO content of 2.7wt% and a specific surface area of ​​545m 2 / kg;

[0048] S3: weigh γ-glycidyloxypropyltrimethoxysilane at 1% of the total mass of the steel slag powder;

[0049] S4: First weigh 3% of steel slag powder, then add γ-glycidyloxypropyltrimethoxysilane, mix evenly, and then put it in a ball mill with the remaining amount of steel slag powder for 1 hour to obtain modified steel slag powder.

[0050] Embodiment 3:

[0051] A method for preparing modified steel slag powder comprises the following steps:

[0052] S1: Mix quicklime and white slag in a mass ratio of 7:3 to obtain a regulator;

[0053] S2: Steel slag (f-CaO content of 4.2wt%) and a regulator of 18% by weight of the steel slag are mixed evenly and placed in a reaction furnace, heated to 1240°C, kept warm for 35 minutes, and then cooled to room temperature; the obtained steel slag is then crushed and ball-milled to obtain steel slag powder. The steel slag powder is tested to have an f-CaO content of 3.2wt% and a specific surface area of ​​500m 2 / kg;

[0054] S3: weigh γ-methacryloxypropyltrimethoxysilane which is 1.2% of the total mass of the steel slag powder;

[0055] S4: First weigh 3% of steel slag powder, then add γ-methacryloxypropyltrimethoxysilane, mix evenly, and then put it in a ball mill with the remaining amount of steel slag powder for 1 hour to obtain modified steel slag powder.

[0056] Embodiment 4:

[0057] A method for preparing a chopped basalt fiber-loaded carbon sphere composite material comprises the following steps:

[0058] (1) Short-cut basalt fibers (length 4.5-5.5 mm, diameter 15-16 μm) were first placed in 3 mol / L hydrochloric acid and heated to 45°C for 3.5 h, filtered, washed with water, and then placed in 1.5 mol / L sodium hydroxide solution for 30 min, then filtered, washed with water, and dried to obtain pretreated basalt fibers;

[0059] (2) dispersing the pretreated chopped basalt fibers in a 1 mol / L glucose aqueous solution, wherein the mass ratio of the 1 mol / L glucose aqueous solution to the pretreated chopped basalt fibers is 30:1; transferring the mixture to a reactor after stirring and mixing, sealing the reactor, and firstly performing a hydrothermal reaction at 195° C. for 40 h; then cooling the mixture to room temperature, and filtering the mixture to obtain an intermediate product;

[0060] (3) The intermediate product was then dispersed in a 0.1 mol / L glucose aqueous solution, wherein the mass ratio of the 0.1 mol / L glucose aqueous solution to the pretreated chopped basalt fiber was 30:1; after stirring and mixing, the mixture was transferred to a reactor, which was sealed and subjected to a hydrothermal reaction at 170°C for 12 h; the mixture was then cooled to room temperature, filtered, washed with water, and vacuum dried to obtain a chopped basalt fiber-loaded carbon ball composite material.

[0061] Embodiment 5:

[0062] A method for preparing a chopped basalt fiber-loaded carbon sphere composite material comprises the following steps:

[0063] (1) Short-cut basalt fibers (length 4.5-5.5 mm, diameter 15-16 μm) were first placed in 2 mol / L hydrochloric acid and heated to 50° C. for 4 h, filtered, washed with water, and then placed in 1 mol / L sodium hydroxide solution for 40 min, then filtered, washed with water, and dried to obtain pretreated basalt fibers;

[0064] (2) dispersing the pretreated chopped basalt fibers in a 0.5 mol / L glucose aqueous solution, wherein the mass ratio of the 0.5 mol / L glucose aqueous solution to the pretreated chopped basalt fibers is 30:1; transferring the mixture to a reactor after stirring and mixing, sealing the reactor, and firstly performing a hydrothermal reaction at 200° C. for 48 h; then cooling the mixture to room temperature, and filtering the mixture to obtain an intermediate product;

[0065] (3) The intermediate product was then dispersed in a 0.3 mol / L glucose aqueous solution, wherein the mass ratio of the 0.3 mol / L glucose aqueous solution to the pretreated chopped basalt fiber was 30:1; after stirring and mixing, the mixture was transferred to a reactor, which was sealed and subjected to a hydrothermal reaction at 160°C for 10 h; the mixture was then cooled to room temperature, filtered, washed with water, and vacuum dried to obtain a chopped basalt fiber-loaded carbon ball composite material.

[0066] Embodiment 6:

[0067] A method for preparing a chopped basalt fiber-loaded carbon sphere composite material comprises the following steps:

[0068] (1) chopped basalt fibers (length 4.5-5.5 mm, diameter 13-14 μm) were first placed in 3 mol / L hydrochloric acid and heated to 45°C for 3 h, filtered, washed with water, and then placed in 1 mol / L sodium hydroxide solution for 50 min, then filtered, washed with water, and dried to obtain pretreated basalt fibers;

[0069] (2) dispersing the pretreated chopped basalt fibers in a 0.8 mol / L glucose aqueous solution, wherein the mass ratio of the 0.8 mol / L glucose aqueous solution to the pretreated chopped basalt fibers is 30:1; transferring the mixture to a reactor after stirring and mixing, sealing the reactor, and firstly performing a hydrothermal reaction at 190° C. for 45 h; then cooling the mixture to room temperature, and filtering the mixture to obtain an intermediate product;

[0070] (3) The intermediate product is then dispersed in a 0.3 mol / L glucose aqueous solution, wherein the mass ratio of the 0.3 mol / L glucose aqueous solution to the pretreated chopped basalt fiber is 30:1; after stirring and mixing, the mixture is transferred to a reactor, which is sealed and subjected to a hydrothermal reaction at 170°C for 10 h; the mixture is then cooled to room temperature, filtered, washed with water, and vacuum dried to obtain a chopped basalt fiber-loaded carbon ball composite material.

[0071] Embodiment 7:

[0072] A low-carbon concrete resistant to thermal shrinkage cracking comprises the following raw materials in parts by weight: 205 parts of gel material, 380 parts of fine aggregate, 430 parts of coarse aggregate, 20 parts of short-cut basalt fiber-loaded carbon ball composite material, 1.3 parts of sodium gluconate, 1 part of polycarboxylic acid water reducer, and 68 parts of water.

[0073] In this embodiment, the gel material includes the following raw materials in weight percentage: 35% modified steel slag powder, 1% Class I fly ash, and the balance is P·O 42.5 ordinary Portland cement; wherein the modified steel slag powder is prepared by the method in Example 2.

[0074] The fine aggregate is composed of river sand and machine-made sand in a mass ratio of 1:1; the fineness modulus of the river sand is 2.8, and the fineness modulus of the machine-made sand is 2.7; the coarse aggregate is 5-25 mm continuously graded crushed stone; the chopped basalt fiber-loaded carbon ball composite material is prepared by the method in Example 6.

[0075] The preparation method of the low-carbon concrete resistant to thermal shrinkage cracking in this embodiment comprises the following steps:

[0076] Water is added to the gel material and stirred for 5 minutes, and then fine aggregate and coarse aggregate are added and stirred for 4 minutes. Then, short-cut basalt fiber-loaded carbon ball composite material, sodium gluconate and polycarboxylic acid water reducer are added and stirred for 3 minutes to obtain the thermal shrinkage cracking resistant low-carbon concrete.

[0077] Embodiment 8:

[0078] A low-carbon concrete resistant to thermal shrinkage cracking comprises the following raw materials in parts by weight: 200 parts of gel material, 340 parts of fine aggregate, 420 parts of coarse aggregate, 19 parts of short-cut basalt fiber-loaded carbon ball composite material, 1.3 parts of sodium gluconate, 0.8 parts of polycarboxylic acid water reducer, and 67 parts of water.

[0079] In this embodiment, the gel material includes the following raw materials in weight percentage: 30% modified steel slag powder, 3% Class I fly ash, and the balance is P·O 42.5 ordinary Portland cement; wherein the modified steel slag powder is prepared by the method in Example 3.

[0080] The fine aggregate is composed of river sand and machine-made sand in a mass ratio of 1:1; the fineness modulus of the river sand is 2.6, and the fineness modulus of the machine-made sand is 2.9; the coarse aggregate is 5-25 mm continuously graded crushed stone; the chopped basalt fiber-loaded carbon ball composite material is prepared by the method in Example 4.

[0081] The preparation method of the low-carbon concrete resistant to thermal shrinkage cracking in this embodiment comprises the following steps:

[0082] Water is added to the gel material and stirred for 4 minutes, and then fine aggregate and coarse aggregate are added and stirred for 5 minutes. Then, short-cut basalt fiber-loaded carbon ball composite material, sodium gluconate and polycarboxylic acid water reducer are added and stirred for 4 minutes to obtain the thermal shrinkage cracking resistant low-carbon concrete.

[0083] Embodiment 9:

[0084] A low-carbon concrete resistant to thermal shrinkage cracking comprises the following raw materials in parts by weight: 210 parts of gel material, 360 parts of fine aggregate, 450 parts of coarse aggregate, 25 parts of short-cut basalt fiber-loaded carbon ball composite material, 1.4 parts of sodium gluconate, 1.3 parts of polycarboxylate water reducer, and 70 parts of water.

[0085] In this embodiment, the gel material includes the following raw materials in weight percentage: 33% modified steel slag powder, 3% Class I fly ash, and the balance is P·O 42.5 ordinary Portland cement; wherein the modified steel slag powder is prepared by the method in Example 1.

[0086] The fine aggregate is composed of river sand and machine-made sand in a mass ratio of 1:1; the fineness modulus of the river sand is 2.8, and the fineness modulus of the machine-made sand is 2.9; the coarse aggregate is 5-25 mm continuously graded crushed stone; the chopped basalt fiber-loaded carbon ball composite material is prepared by the method in Example 5.

[0087] The preparation method of the low-carbon concrete resistant to thermal shrinkage cracking in this embodiment comprises the following steps:

[0088] Water is added to the gel material and stirred for 5 minutes, and then fine aggregate and coarse aggregate are added and stirred for 5 minutes. Then, short-cut basalt fiber-loaded carbon ball composite material, sodium gluconate and polycarboxylic acid water reducer are added and stirred for 3 minutes to obtain the thermal shrinkage cracking resistant low-carbon concrete.

[0089] Embodiment 10:

[0090] A low-carbon concrete resistant to thermal shrinkage cracking comprises the following raw materials in parts by weight: 215 parts of gel material, 360 parts of fine aggregate, 420 parts of coarse aggregate, 18 parts of short-cut basalt fiber-loaded carbon ball composite material, 1.2 parts of sodium gluconate, 1.1 parts of polycarboxylic acid water reducer, and 70 parts of water.

[0091] In this embodiment, the gel material includes the following raw materials in weight percentage: 34% modified steel slag powder, 2% Class I fly ash, and the balance is P·O 42.5 ordinary Portland cement; wherein the modified steel slag powder is prepared by the method in Example 2.

[0092] The fine aggregate is composed of river sand and machine-made sand in a mass ratio of 1:1; the fineness modulus of the river sand is 2.6, and the fineness modulus of the machine-made sand is 2.7; the coarse aggregate is 5-25 mm continuously graded crushed stone; the chopped basalt fiber-loaded carbon ball composite material is prepared by the method in Example 5.

[0093] The preparation method of the low-carbon concrete resistant to thermal shrinkage cracking in this embodiment is the same as that in Example 7.

[0094] Embodiment 11:

[0095] A low-carbon concrete resistant to thermal shrinkage cracking comprises the following raw materials in parts by weight: 220 parts of gel material, 350 parts of fine aggregate, 450 parts of coarse aggregate, 22 parts of short-cut basalt fiber-loaded carbon ball composite material, 1.5 parts of sodium gluconate, 1 part of polycarboxylic acid water reducer, and 72 parts of water.

[0096] In this embodiment, the gel material includes the following raw materials in weight percentage: 30% modified steel slag powder, 5% Class I fly ash, and the balance is P·O 42.5 ordinary Portland cement; wherein the modified steel slag powder is prepared by the method in Example 1.

[0097] The fine aggregate is composed of river sand and machine-made sand in a mass ratio of 1:1; the fineness modulus of the river sand is 2.6, and the fineness modulus of the machine-made sand is 2.9; the coarse aggregate is 5-25 mm continuously graded crushed stone; the chopped basalt fiber-loaded carbon ball composite material is prepared by the method in Example 4.

[0098] The preparation method of the low-carbon concrete resistant to thermal shrinkage cracking in this embodiment is the same as that in Example 9.

[0099] Embodiment 12:

[0100] A low-carbon concrete resistant to thermal shrinkage cracking comprises the following raw materials in parts by weight: 210 parts of gel material, 370 parts of fine aggregate, 430 parts of coarse aggregate, 19 parts of short-cut basalt fiber-loaded carbon ball composite material, 1.2 parts of sodium gluconate, 1.3 parts of polycarboxylic acid water reducer, and 69 parts of water.

[0101] In this embodiment, the gel material includes the following raw materials in weight percentage: 30% modified steel slag powder, 5% Class I fly ash, and the balance is P·O 42.5 ordinary Portland cement; wherein the modified steel slag powder is prepared by the method in Example 1.

[0102] The fine aggregate is composed of river sand and machine-made sand in a mass ratio of 1:1; the fineness modulus of the river sand is 2.8, and the fineness modulus of the machine-made sand is 2.7; the coarse aggregate is 5-25 mm continuously graded crushed stone; the chopped basalt fiber-loaded carbon ball composite material is prepared by the method in Example 6.

[0103] The preparation method of the low-carbon concrete resistant to thermal shrinkage cracking in this embodiment is the same as that in Example 8.

[0104] Comparative Example 1:

[0105] The difference from Example 12 is that the chopped basalt fiber-loaded carbon ball composite material is replaced by chopped basalt fibers (with a length of 4.5-5.5 mm and a diameter of 13-14 μm).

[0106] Comparative Example 2:

[0107] Different from Example 12, the short basalt fiber-loaded carbon sphere composite material is prepared by the following method:

[0108] Short chopped basalt fibers (length 4.5-5.5 mm, diameter 13-14 μm) were dispersed in a 0.4 mol / L glucose aqueous solution, stirred and mixed, and then transferred to a reactor. The reactor was sealed and first subjected to a hydrothermal reaction at 190°C for 20 hours. The fibers were then cooled to room temperature, filtered, and vacuum dried to obtain a short basalt fiber-loaded carbon ball composite material.

[0109] Comparative Example 3:

[0110] Different from Example 12, the gel material includes the following raw materials in weight percentage: 30% steel slag powder, 5% Class I fly ash, and the balance P·O 42.5 ordinary Portland cement; wherein the steel slag powder is prepared by the following method: crushing and ball milling steel slag (f-CaO content is 4.2wt%) to obtain steel slag powder with a specific surface area of ​​about 560m 2 / kg.

[0111] Comparative Example 4:

[0112] Different from Example 12, the method for preparing the modified steel slag powder in the gel material comprises the following steps:

[0113] S1: mixing quicklime and white slag in a mass ratio of 1:1 to obtain a regulator;

[0114] S2: Steel slag (f-CaO content of 4.2wt%) and a regulator of 20% by weight of the steel slag are mixed evenly and placed in a reaction furnace, heated to 1330°C, kept warm for 50 minutes, and then cooled to room temperature; the obtained steel slag is then crushed and ball-milled to obtain steel slag powder. The steel slag powder is tested to have an f-CaO content of 1.0wt%, and a specific surface area of ​​about 560m 2 / kg;

[0115] S3: weigh γ-glycidyloxypropyltrimethoxysilane which is 1.5% of the total mass of the steel slag powder;

[0116] S4: First weigh 4% of steel slag powder, then add γ-glycidyloxypropyltrimethoxysilane, mix evenly, and then put it in a ball mill with the remaining amount of steel slag powder for 1 hour to obtain modified steel slag powder.

[0117] Comparative Example 5:

[0118] The difference from Example 12 is that the chopped basalt fiber-loaded carbon ball composite material is replaced by chopped basalt fibers (with a length of 4.5-5.5 mm and a diameter of 13-14 μm).

[0119] The gel material includes the following raw materials in weight percentage: 30% steel slag powder, 5% grade I fly ash, and the balance P·O42.5 ordinary Portland cement; wherein the steel slag powder is prepared by the following method: crushing and ball milling steel slag (f-CaO content is 4.2) to obtain steel slag powder with a specific surface area of ​​about 560m 2 / kg.

[0120] test:

[0121] The concrete prepared in Examples 7-12 and Comparative Examples 1-5 was tested for 28d compressive strength and 28d flexural strength according to GB / T50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete". During the test, a test block of 100mm×100mm×100mm was prepared and cured for 28d. In addition, the 28d shrinkage value was tested according to the shrinkage test in GBJ82-85 "Test Methods for Long-term Performance and Durability of Ordinary Concrete". In addition, the crack conditions on the crack surface of the test block were checked. The specific test results are shown in Table 1.

[0122] Table 1 Concrete performance test results

[0123]

[0124] It can be seen from Table 1 that the 28d shrinkage values ​​of the concretes prepared in Examples 7-12 and Comparative Examples 1-5 are relatively low and not prone to cracking. On the basis of adding a large amount of modified steel slag powder, they have higher 28d compressive strength and 28d flexural strength.

[0125] From the comparison between Comparative Example 1 and Example 12, it can be seen that if the short basalt fiber loaded carbon ball composite material is not modified by carbon balls, the strength of the concrete will be significantly reduced, and the thermal shrinkage resistance will be reduced. From the comparison between Comparative Example 2 and Example 12, it can be seen that when preparing the short basalt fiber loaded carbon ball composite material, the carbon balls are directly loaded on the surface of the untreated short basalt fibers in one step, and the initial concentration of the glucose aqueous solution and the hydrothermal reaction time are reduced, the performance of the obtained short basalt fiber loaded carbon ball composite material will be reduced, thereby affecting the strength and thermal shrinkage resistance of the obtained concrete.

[0126] From the comparison between Comparative Example 3 and Example 12, it can be seen that if unmodified steel slag powder is used to prepare the gel material, the strength of the obtained concrete will be significantly reduced. From the comparison between Comparative Example 4 and Example 12, it can be seen that if the f-CaO content in the modified steel slag powder is small, the strength of the obtained concrete is higher, but its anti-thermal shrinkage performance will be reduced.

[0127] From the comparison between Comparative Example 5 and Example 12, it can be seen that if the steel slag powder is not modified and only the original chopped basalt fiber is used as the reinforcing fiber when preparing concrete, the strength of the obtained concrete will be significantly reduced, the shrinkage resistance will be reduced, cracks will appear, and the overall quality of the concrete will be significantly reduced.

[0128] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A low-carbon concrete resistant to thermal shrinkage cracking, characterized in that: The invention comprises the following raw materials in parts by weight: 200-220 parts of gel material, 340-380 parts of fine aggregate, 420-450 parts of coarse aggregate, 18-25 parts of short-cut basalt fiber-loaded carbon ball composite material, 1.2-1.5 parts of retarder, 0.8-1.3 parts of polycarboxylate water reducer and 67-72 parts of water.

2. The low-carbon concrete resistant to thermal shrinkage cracking according to claim 1, characterized in that: The gel material comprises the following raw materials in weight percentage: 30-35% of modified steel slag powder, 1-5% of fly ash, and the balance of cement.

3. The low-carbon concrete resistant to thermal shrinkage cracking according to claim 2, characterized in that: The preparation method of the modified steel slag powder comprises the following steps: S1: Mix quicklime and white slag in a mass ratio of 7-8:2-3 to obtain a regulator; S2: The steel slag is mixed evenly with a regulator of 17-20% of the mass of the steel slag, and then placed in a reaction furnace, heated to 1240-1260°C, and kept warm for 30-40 minutes, and then cooled to room temperature; the obtained steel slag is then crushed and ball-milled to obtain steel slag powder; S3: weighing 1-1.5% of the total mass of the steel slag powder as a silane coupling agent; S4: First weigh 3-4% of steel slag powder, then add silane coupling agent, mix evenly, and then mix with the remaining amount of steel slag powder in a ball mill to obtain the modified steel slag powder.

4. The low-carbon concrete resistant to thermal shrinkage cracking according to claim 3 is characterized in that: The content of f-CaO in the steel slag powder is 2.7-3.2wt%; the specific surface area of ​​the modified steel slag powder is 500-560m 2 / kg; The silane coupling agent is one or more of γ-glycidyloxypropyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane.

5. The low-carbon concrete resistant to thermal shrinkage cracking according to claim 2, characterized in that: The cement is silicate cement, and the fly ash is Class I fly ash or Class II fly ash.

6. The low-carbon concrete resistant to thermal shrinkage cracking according to claim 1, characterized in that: The preparation method of the short-cut basalt fiber-loaded carbon ball composite material comprises the following steps: (1) pretreating the chopped basalt fibers to obtain pretreated chopped basalt fibers; (2) dispersing the pretreated chopped basalt fibers in a 0.5-1 mol / L glucose aqueous solution, stirring and mixing, transferring the mixture to a reactor, sealing the reactor, and first performing a hydrothermal reaction at 190-200° C. for 40-48 h; then cooling the mixture to room temperature, and filtering the mixture to obtain an intermediate product; (3) The intermediate product is then dispersed in a 0.1-0.3 mol / L glucose aqueous solution, stirred and mixed, and then transferred to a reactor. The reactor is sealed and first subjected to a hydrothermal reaction at 160-170° C. for 10-12 h. The mixture is then cooled to room temperature, filtered, washed with water, and vacuum dried to obtain a chopped basalt fiber-loaded carbon ball composite material.

7. The low-carbon concrete resistant to thermal shrinkage cracking according to claim 6, characterized in that: The step (1) specifically comprises the following steps: placing the chopped basalt fibers in a hydrochloric acid solution with a concentration of 2-3 mol / L and heating it to 45-50° C. for 3-4 hours, filtering and washing it with water, and then placing it in a sodium hydroxide solution with a concentration of 1-1.5 mol / L for 30-50 minutes, and then filtering, washing it with water, and drying it to obtain pretreated basalt fibers.

8. The low-carbon concrete resistant to thermal shrinkage cracking according to claim 7, characterized in that: The length of the chopped basalt fibers is 4.5-5.5 mm, and the diameter is 13-16 μm.

9. The low-carbon concrete resistant to thermal shrinkage cracking according to claim 1, characterized in that: The fine aggregate is composed of river sand and machine-made sand in a mass ratio of 1-2:1-2; The fineness modulus of the river sand is 2.6-2.8; the fineness modulus of the machine-made sand is 2.7-2.9; The coarse aggregate is 5-25 mm continuously graded crushed stone; The retarder is sodium gluconate.

10. The method for preparing low-carbon concrete resistant to thermal shrinkage cracking according to any one of claims 1 to 9, characterized in that: The following steps are involved: Add water to the gel material and stir for 4-5 minutes, then add fine aggregate and coarse aggregate, continue stirring for 4-5 minutes, then add short-cut basalt fiber-loaded carbon ball composite material, retarder, and polycarboxylate water reducer, stir and mix for 3-4 minutes to obtain the thermal shrinkage cracking resistant low-carbon concrete.